PERAN KEPUASAN KERJA MEMEDIASI MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA GURU SEKOLAH DASAR ( Studi pada UPT Dinpendik Kecamatan Sumber Kabupaten Rembang ) - Agus Buharwoto, 12.52.02.0044; Suhari, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to analyze the influence of work motivation and work discipline on the performance of elementary school teachers job satisfaction mediated. Location of the study in the Technical Implementation Unit Office of the District Educational Resources District Apex. In this study population of 194 with a sample of 121 respondents with a purposive sampling method. With a minimum education level criterion D2, minimum age 21 years, minimum term of 4 years, and rank / class minimum gelongan II. Measurements using a Likert scale of 7 (seven) jawaban.Uji alternative instruments used are validity and reliability, while the test model used is the coefficient of determination, F test (Goodness of Fit) and t test (t-test). Hypothesis test used in this study is a regression analysis with the t criteria. Hypothesis testing used the t test at significance level frequency distribution (a) 5%. The results showed 85.6% of the change can be explained by the variable performance of work motivation, work discipline and job satisfaction was 14.4% outside of the model is described. The results of the hypothesis test result that (1) does not affect the work motivation of teachers job satisfaction, (2) the discipline of work have a significant effect on job satisfaction of teachers, (3) work motivation have a significant effect on teacher performance, (4) job satisfaction significantly the effect on performance teacher Keywords: Work Motivation, Work Discipline, Kepuasann Work, and Teacher           Performance